2019
DOI: 10.1007/s12975-019-0691-x
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of Directly Reprogrammed Human Neural Precursor Cells Following Stroke Promotes Synaptogenesis and Functional Recovery

Abstract: Stroke is one of the leading causes of long-term disability. Cell transplantation is a promising strategy to treat stroke. We explored the efficacy of directly reprogrammed human neural precursor cell (drNPC) transplants to promote functional recovery in a model of focal ischemic stroke in the mouse sensorimotor cortex. We show that drNPCs express neural precursor cell markers and are neurally committed at the time of transplantation. Mice that received drNPC transplants recovered motor function, irrespective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 56 publications
8
36
0
Order By: Relevance
“…The endothelin-1 model of cortical injury produced reproducible lesions with small but significant motor deficits that were detectable using gait analysis until PSD 63 (the longest time examined), and lesion volumes similar to those reported previously [26,27]. Endohelin-1 is a commonly used preclinical model of ischemic stroke as it mimics the pathophysiological processes that are more closely related to the clinical condition, including excitotoxicity, generation of reactive oxygen species, related inflammatory responses, and gliosis [28,29].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The endothelin-1 model of cortical injury produced reproducible lesions with small but significant motor deficits that were detectable using gait analysis until PSD 63 (the longest time examined), and lesion volumes similar to those reported previously [26,27]. Endohelin-1 is a commonly used preclinical model of ischemic stroke as it mimics the pathophysiological processes that are more closely related to the clinical condition, including excitotoxicity, generation of reactive oxygen species, related inflammatory responses, and gliosis [28,29].…”
Section: Discussionsupporting
confidence: 67%
“…ET-1 (Calbiochem) was used to induce stroke as previously described [27,49]. Mice were anesthetized using isoflurane and mounted onto a stereotaxic apparatus.…”
Section: Endothelin-1 (Et-1) Strokementioning
confidence: 99%
“…Previous studies have shown that the engraftment and differential potential of transplanted ESCor iPSC-derived NPCs were highly variable. Approximately 5~30% of cells survive 4 weeks after transplantation, with the numbers of engrafted cells gradually decreasing thereafter [15,[17][18][19][20][33][34][35][36]. Even if the cells had survived, the number of differentiated neurons among the grafted cells was low in this study (less than 10% of engrafted cells).…”
Section: Stem Cells Internationalmentioning
confidence: 54%
“…Besides, we found the formation of cholinergic and glutamatergic neurons in the transplanted COs that are important for the regulation of neurotransmitter release. Transplanted cells can form functional synaptic inputs into host brain [40,41]. Along with extensive expression of synaptic connection-related proteins in the host brain, we found that some of them have gradually increased overlap with cells from transplanted COs, indicating synaptic connection between transplanted COs and host brain after stroke.…”
Section: The Mechanism Of Cos Transplantation In Strokementioning
confidence: 76%
“…Transplanted cells have been reported to reduce cell death and provide growth/trophic support to enhance endogenous regeneration via paracrine action in the host brain [4,41]. With examination of neurogenesis in the host brain, COs transplantation significantly enhances neurogenesis in the ipsilateral cortex, SGZ, and SVZ after MCAO.…”
Section: The Mechanism Of Cos Transplantation In Strokementioning
confidence: 99%